(3cJGH HQD GdSGYIs - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3gPG cJGH Cdag eMeO Hf RcQjG GdQGRi ai GdWH hJQLeJg HHQD SGYI hYedJ gPG GdcJGH hGLJgOJ ajg hSejJg HQD SGYI hgh eKd cJGH GdSQ ai GdUfYI s
(3BNQgG (B:s
(3ajg ca edM hjTY CWQGag ajg SGYI aEfg jScf ai GdhbJ hEP bO CJjfG Ydi eG bUOfG Edjg afbhd dGMhd hdG bhI EdG HGddg GdYdi GdYXje Je GdcJGH HYhf Gddg Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdWHs